Analisis tekno-ekonomi proses pemisahan fraksi jenuh dan fraksi tak jenuh dari distilat asam lemak sawit - Halim, Fadhli; Indarto, Antonius; Putrawan, I Dewa Gede Arsa (Jurnal Rekayasa Proses, 2025)
Palm fatty acid distillate (PFAD) can be used as a raw material for two types of polyvinyl chloride (PVC) thermal stabilizers: organotin and mixed organometal. To produce high-quality thermal stabilizers, PFAD must first be separated into saturated and unsaturated fractions. This research aims to develop and analyze the techno-economics of separating these fractions from PFAD through solvent crystallization using methanol. The study began with the development of a process flow diagram, including the selection of unit operations and equipment. Mass and energy balances for the developed process were then calculated. Investment and production costs were estimated and used to determine economic indicators. These calculations were performed using Aspen Plus and Aspen Hysys software. Utility requirements were primarily driven by solvent evaporation and condensation. From an environmental perspective, higher crystallization temperatures are preferable due to reduced fuel consumption and lower CO2 emissions. However, higher crystallization temperatures resulted in a less pure unsaturated fraction, despite producing a larger quantity. The estimated investment for constructing a separation plant with the studied capacity and crystallization temperature range was between 13.6 and 13.9 million USD. Among the equipment, fired heaters and refrigeration compressors contribute the most to costs. The separation process at temperatures of -15°C and 0°C was found to be economically viable, with internal rates of return (IRR) of 36% and 49%, respectively. In contrast, the separation process at 10°C was not economically feasible. The findings of this study are expected to serve as a reference for the development of commercial-scale processes.